Bifunctional Dalteparin/Enoxaparin coated nanosilver formulation to prevent bloodstream infections during hemodialysis. (1st September 2022) - Meher, Mukesh Kumar; Poluri, Krishna Mohan
Abstract: Catheter-related bloodstream infections (CRBSI) are the major concern of patients undergoing hemodialysis. The current study formulates bifunctional low molecular weight heparin (LMWH) coated nanosilver as an effective anticoagulant and antimicrobial/anti-biofilm agent. Nanosilver formulations were prepared using a microwave-assisted green synthesis approach and stabilized with pharmaceutically approved LMWH such as dalteparin (DL) and enoxaparin (EX) along with unfractionated heparin (HP) as a control. The obtained heparinized (HP/DL/EX) nanosilver was monodisperse, and the size ranged between 15 and 25 nm. DL/EX predominantly stabilized the nanosilver by primarily engaging their negatively charged sulfate groups. The obtained DL/EX coated nanosilver are hemocompatible, showed two times increase in their anticoagulation activity, and are highly potent in inhibiting/eradicating both mono- and polymicrobial biofilms. Henceforth, the observed biocompatible and enhanced bifunctional characteristics of DL/EX coated nanosilver can be used to replace the systemic antibiotics and can be an alternative catheter lock solution to prevent CRBSI in hemodialysis therapy. Graphical abstract: Unlabelled Image